Kidney, thyroid and other organ functions after 40 years or more of lithium therapy: a case series of five patients. (August 2016) - Permoda-Osip, Agnieszka; Abramowicz, Maria; Kraszewska, Agnieszka; Suwalska, Aleksandra; Chlopocka-Wozniak, Maria; Rybakowski, Janusz K.
We present the cases of five patients (two men aged 64 years and 79 years) and three women (aged 64 years, 65 years and 75 years) who have received lithium treatment for 40–45 years, with particular regard to kidney and thyroid functions, hypercalcaemia and cognition, in the context of disease course and overall functioning. Lithium was initiated in the early phase of the illness (in three patients within the first 2 years). In four patients, lithium concentration was between 0.60 and 0.65 mmol/l and in one patient, between 0.7 and 0.8 mmol/l. Four were very good lithium responders. One man had stage 3 chronic kidney disease, and the other stage 2/3 chronic kidney disease. All three women had asymptomatic stage 2 chronic kidney disease. One woman had severe thyroid dysfunction (Hashimoto's disease) with extremely high levels of antithyroid peroxidase antibodies and antithyroglobulin antibodies and was receiving thyroxine. Serum calcium levels were normal or borderline in all five patients, and most cognitive functions were comparable to healthy persons of similar gender, age and years of education. All the patients were professionally active until 55–65 years and their family and social functioning were satisfactory. It was concluded that, in good lithium responders, ultra-long-term treatment with lithium enables good professional and psychosocial functioning, and the possible somatic side effects are manageable.